Change of treatment guidelines and evolution of ART initiation in rural South Africa: data of a large HIV care and treatment programme - (:unkn) unknown (My University, 2015)
Background: While WHO recommendations are to treat people earlier and earlier, it will considerably increase the number of HIV infected people eligible for antiretroviral therapy (ART). In South Africa, a country which carries one of the highest HIV burden worldwide, very few studies are available on the impact of the ART guidelines on time to ART initiation in both individuals with low CD4 count and those newly eligible for ART. We thus aimed to describe ART initiation percentages in a large HIV programme in rural KwaZulu-Natal, South Africa, according to the temporal changes of national ART eligibility guidelines from 2007 to 2012. Methods: Adults who accessed the decentralized Hlabisa HIV treatment programme in 2007–2012 were included. Three periods following the temporal change of ART eligibility guidelines were defined (Period 1: until). Percentages of ART initiation within three months of programme entry were estimated in men, in women of childbearing age (<40 years old) and in older women, and stratifying by CD4 count. Trend tests and logistic regression models were used to study the effects of change of guidelines on ART initiation percentages. Results: In individuals with CD4 count ≤200 cells/μL (N = 5709 men, N = 6743 women <40 years old and N = 2017 older women), percentages of ART initiation did not differ over time (p trend = 0.25; 0.28; and 0.14, respectively). In individuals with CD4 count = 201–350 cells/μL (N = 2680 men, N = 6086 women <40 years old and N = 1415 older women), percentages of ART initiation significantly increased over time (p trend <0.01 for the three groups): from 6 % in Period 1 to 20 % in Period 2 to 40 % in Period 3 in women of childbearing age, and from 7 % to 8-10 % to 42 % in men and in older women.Conclusions : As temporal changes of guidelines, percentages of ART initiation significantly increased in newly ART eligible people and did not decrease in individuals with very low
Keywords: African Research